Pencapaian Tujuan Pendidikan Berbasis Hasil (OBE) Dan Strategi Pembelajaran Mandiri Pendidikan Islam: Studi Pilot - Ahmad Firdaus Bin Mohd Noor; Khairunnisa A Shukor; Nur Afifah Saharudin (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
The OBE approach has already been practised in educational institutions in Malaysia, whether in primary, secondary, or higher education. The use of the OBE approach has become an alternative to traditional educational methodology, which prepares the students before entering the working world and to face the challenges of life after completing their studies. This study was conducted to measure the influence of the OBE approach on the Islamic Studies I course OBE achievement. 30 students who have taken the Islamic Studies I course in polytechnics have participated in this study. A set of questionnaires was used to obtain quantitative data and the data were analysed using SPSS 17. 0. The findings show that the contribution of self-regulated learning strategies towards the grade of Islamic Studies I was 13. 9%. Strategies frequently used by the respondents include; studying with friends, repeating and organizing. However, repeating has mostly contributed to the grade and followed by studying with friends. It is because students need to memorize verses and recitation of the daily prayers for the practical test. Islamic Studies I also involves group assignments which leads to the study groups approach. In conclusion, self-learning strategies have minimally contributed to achieving OBE.